Bahasa Persuasif Digunakan Oleh Nick Vujcic Dalam Video Youtube - Zanura, Lara; Siska, Siska; Syafar, Dian Noviani (EduCurio: Education Curiosity, 2023)
Persuasive language is communication language that aims to influence the reader's feelings to do and believe according to the statement conveyed. Persuasive language can be found in everyday conversations including in videos. This research aims to see how effective persuasion language used by Nick Vujicic in YouTube videos using the theory of Conger & June (1998). The data source in this study is a video taken from Nick Vujicic's YouTube with the title Champions for the bullied with Nick Vujicic. The researcher used a qualitative method with the technique of free listening and note-taking as a follow-up technique. The data used in the form of transcripts were classified in the form of persuasive sentences based on the criteria. The results showed that the researcher found four specific effective persuasive steps in Nick's video, namely; establish credibility, common ground, provide evidence, and connect emotionally. From this study it can be concluded that persuasive sentences involve four important steps found in Nick's video so that they are effective persuasive sentences.